Revelation of Diabetics by Inadequate Balanced SVM - et. al., Dr G Revathy , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetic Irish (DI) is human eye disease among people with diabetics which causes damage to irish of eye and may eventually lead to complete blindness. Detection of diabetic Irish in early stage is essential to avoid complete blindness. It will give us accuracy of which algorithm will be suitable and more accurate for prediction of the disease. To maintain more accuracy we follow feature extraction using SVM which gives 85% accuracy results compared with previous techniques.